ASR prevention — Effect of aluminum and lithium ions on the reaction products. (October 2015) - Leemann, Andreas; Bernard, Laetitia; Alahrache, Salaheddine; Winnefeld, Frank
Abstract: In spite of the recent progress in the understanding of the mechanisms enabling aluminum-containing SCM like metakaolin and added LiNO3 to limit the extent of ASR in mortar and concrete, some gaps still remain. They concern mainly the effect of aluminum-containing SCM on the formed ASR products and the influence of aggregate characteristics on the effectiveness of LiNO3 . In this study, a model system, concrete and mortar were investigated by pore solution analysis, TGA, XRD, NMR, SEM combined with EDX and ToF-SIMS to address these questions. The amount of aluminum present in the pore solution of concrete and mortar is only able to slow down SiO2 dissolution but not to alter morphology, structure and composition of the reaction products. LiNO3 can suppress ASR by forming dense products protecting reactive minerals from further reaction. But its effectiveness is decreasing with increasing specific surface area of the reactive minerals in aggregates. Highlights: Aluminum of SCM slows down SiO2 dissolution. Aluminum of SCM does not alter morphology and structure of ASR product. ASR suppressing effect of LiNO3 depends on specific surface area of the aggregates.